Children's expectancy beliefs and subjective task values through two years of school-based program and associated links to physical education enjoyment and physical activity - Arto Gråstén (Elsevier, 2016)
Purpose: The present study examined the patterns of children's expectancy beliefs and subjective task values through the Physical Activity as Civil Skill Program and associated links to physical education enjoyment and total physical activity. Methods: The sample comprised 401 children aged 9-13 years from 3 small towns located in North-East Finland. All children received school-based activities across 2-year program from Grades 5 to 7. The present data were collected using questionnaires across 3 measurement phases during 2012-2014. Results: The levels of expectancy beliefs and subjective task values indicated to be relatively high and the development was stable through the program, especially in terms of expectancy beliefs, attainment value, and cost. In contrast, interest value and utility value decreased over the particular period of time. Boys believed they are physically more competent when compared to other students and valued physical education classes more important than girls. In addition, the higher the physical activity level the children reported, the higher the physical education enjoyment they perceived. Conclusion: The current program including actions to increase physical activity through manipulation of psychological and physical school environment modifications indicated to be an effective strategy to prohibit declining levels of children's expectancy beliefs and task values. Keywords: Exercise motivation, Expectancy beliefs, Expectancy-value theory, Physical activity, Physical education enjoyment, Task values